Shifting Security Left: A Guide to Cybersecurity Education for Children - Sundar Subramanian (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article investigates the effectiveness of tailored cybersecurity education frameworks for children and adolescents. It explores how structured learning approaches, gamified platforms, and family engagement strategies influence learning outcomes. The article, conducted over 18 months, analyzes educational progress across three age groups (7-10, 11-14, and 15-18 years), revealing significant variations in learning effectiveness and retention rates among different age cohorts. Through a systematic evaluation of multiple learning platforms and national initiatives, the research demonstrates that age-appropriate content delivery, gamified learning experiences, and consistent family involvement substantially improve cybersecurity awareness and behavioral outcomes. Key findings include notably high retention rates in elementary students when using visual and interactive content, significant improvements in practical security skills among middle school students, and advanced concept mastery in high school participants. The article also identifies critical challenges in implementation, including resource accessibility gaps, technical barriers, and varying levels of family engagement capability. These insights inform a comprehensive set of recommendations for educational framework improvements, enhanced monitoring strategies, and policy developments, providing a roadmap for advancing children’s cybersecurity education. The findings contribute significantly to understanding how age-appropriate cybersecurity education can be effectively designed and implemented while highlighting the crucial role of family involvement and institutional support in developing secure digital behaviors among young users.